2019
DOI: 10.1155/2019/6210704
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Law and Prediction Model of Dust Concentration under Airflow Adjustment in Fully Mechanized Heading Face

Abstract: The current situation of extensive ventilation management for the fully mechanized heading face cannot dynamically control air velocity and make reasonable dust migration distribution, resulting in serious disaster of dust and environmental pollution in the roadway. In this paper, the fluid mechanics, finite element numerical simulation, and underground measurement were combined to analyze the distribution of dust concentration under the variable airflow state at the duct outlet to obtain the massive correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…At present, wind field regulation rules are calculated using static mining data under different working conditions and do not consider the dynamic characteristics of the data ( Gong et al., 2019b , 2021 ). The static method not only misses the first regulation time but also the effect of the regulation cannot meet the changing needs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, wind field regulation rules are calculated using static mining data under different working conditions and do not consider the dynamic characteristics of the data ( Gong et al., 2019b , 2021 ). The static method not only misses the first regulation time but also the effect of the regulation cannot meet the changing needs.…”
Section: Introductionmentioning
confidence: 99%
“…Ijaz et al gathered health data of workers in five different mines of Pakistan and found that the mine with the lowest ventilation volumetric flow rate has the highest dust concentration (Ijaz et al, 2020). Moreover, Gong et al combined the fluid mechanics, finite element method, and underground measurement and established the doubleobjective BP prediction model to calculate the dust concentration in mines (Gong et al, 2019). Hua et al used the CFD method and studied the effect of the position of the suction channel and the exhaust air rate on the dust diffusion and obtained the optimal dust control parameters (Hua et al, 2020).…”
Section: Introductionmentioning
confidence: 99%